A Novel Multi-analyte Serum Panel Combining CA-125, HE4, microRNA-200a, and Interleukin-6 for the Preclinical Detection of High-Grade Serous Ovarian Carcinoma in Women with Pathogenic *BRCA1/2* Variants: Serum CA-125, HE4, microRNA-200a, and Interleukin- Serous Ovarian Carcinoma - Li, Chanyu; Yang, Zhiling; Xie, Jiaqiong; Long, Yingfei (Journal of Medical Biochemistry, 2026)
Background: Pathogenic *BRCA1/2* variant carriers require effective surveillance for high-grade serous ovarian cancer (HGSOC), a malignancy characterized by late-stage detection and poor prognosis. Current monitoring with CA-125 and transvaginal ultrasound lacks sensitivity for early-stage disease.Objective: To develop and validate a multi-analyte serum panel for the preclinical detection of HGSOC in *BRCA1/2* carriers.Methods: In a prospective, multicenter longitudinal cohort, we enrolled 450 women with pathogenic *BRCA1/2* variants. Serial serum samples were collected every 6 months. The study included 45 incident HGSOC cases and 405 matched controls. Levels of CA-125, HE4, miR-200a, and IL-6 were quantified using immunoassays and RT-qPCR. A composite risk score was derived using logistic regression, and diagnostic performance was evaluated using ROC curve analysis, sensitivity, specificity, and lead-time assessment.Results: All four biomarkers were significantly elevated in pre-diagnostic samples from HGSOC cases (p
Keywords: serum CA-125, HE4, miR-200a, IL-6 ,HGSOC , BRCA